DISCOVERY OF THE NEOPROTEROZOIC MAGMATICS IN SOUTHEASTERN YUNNAN: EVIDENCE FROM SHRIMP ZIRCON U-PB DATING AND LITHOGEOCHEMISTRY - Liu Y.P.; Ye L.; Guo L.G.; Pi D.H.; Li C.Y.; Song B.; Li T.S. (My University, 2006)
The region includes southeastern Yunnan and North Vietnam, which locates among the Nanhua, Yangtze and Indio-China Blocks, is a key target to study the tectonic evolution of South China and Southeastern Asian. There is a deformed-metamorphic dome outcrops in the Laojunshana area, Southeastern Yunnan. It had been divided into the Later Silurian Nanwenhe granite, the Neoproterozoic Xinzhai Formation and the Paleoproterozoic Mengdong Group in the recently 1/50000 regional geological surveys. The SHRIMP zircon U-Pb dating have been done first on the quartz-hornblende-plagiogneiss from the Mengdong Group, and the ages of two magmatic zircon groups are 761 ± 12Ma (N = 11, MSWD = 0.85) and 829 ± 10Ma(N = 10, MSWD = 0.36), respectively. Combined with the crystal features, CL images, concordant of U-Th-Pb ages (the D% are 2.6 and 4.8, respectively) and the correlation index (0.64 and 0.19, respectively), 761 ± 12Ma should present the crystal age, and 829 ± 10Ma should presented the age of an older magmatism. These ages suggested that there should have the Neoproterozoic magmatism in the area, and the Mengdong Group should be a Precambrian metamorphic sedimentary and magmatic complex. Besides these, the inherited zircons with ≈ 1.83Ga U-Pb dating indicated that there should have the paleo-proterozoic basement rocks in this area. The coexist quartz-plagio-amphibolite have rare-earth element and trace element distribution characteristic of OIB, and the quartz-hornblende- plagiogneiss have similar geochemistry characteristics beside low TiO2, P2O5, K2O, Rb, Sr, Eu contents and moderate Nb-Ta negative anomaly, which should be attributed to crystal fraction and crust-contaminate. The geochemistry and tectonic setting identification of these samples suggested that their protolith should be basaltic to basaltic-andesitic magmatic series related to mantle-plume. Based on these mention above, the Laojunshan area, Southeastern Yunnan should located in the cross region of the Nanhua Rift and the Kangdian Rift during breaking-up of the Rodinian Super-continent in the Neoproterozoic.
Keywords: GEOCHEMISTRY; NEOPROTEROZOIC MAGMATISM; SHRIMP ZIRCON U-PB DATING; SOUTHEASTERN YUNNAN; Палеозой::Силурийская; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская; Докембрий::Протерозой::Палеопротерозойская; Paleozoic::Silurian; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic; Precambrian::Proterozoic::Paleoproterozoic